Ethical Implications of the Mild Encephalitis Hypothesis of Schizophrenia - Riedmüller, Rita; Müller, Sabine (Frontiers in Psychiatry, 2017)
Schizophrenia is a serious mental disease with a high mortality rate and severe social consequences. Due to insufficient knowledge about its etiopathogenesis, curative treatments are not available. One of the most promising new research concepts is the Mild Encephalitis Hypothesis of schizophrenia, developed mainly by Karl Bechter and Norbert Müller. According to this hypothesis, a significant subgroup of schizophrenia patients suffer from a mild, but chronic form of encephalitis with markedly different etiologies ranging from viral infections, traumas to autoimmune diseases. This inflammatory process is thought to occur in the beginning or during the course of the disease. In this article, we investigate the consequences of the Mild Encephalitis Hypothesis of schizophrenia for the scientific community, and evaluate these consequences ethically. The Mild Encephalitis Hypothesis implies that schizophrenia would no longer be considered an incurable psychiatric disorder. Instead, it would be considered a chronic, but treatable neurological disease. This paradigm shift would doubtlessly have significant consequences: (1) Major reforms would be necessary in the theoretical conceptualization of schizophrenia, which would challenge the psychiatric diagnostic systems DSM-5 and ICD-10. (2) Psychotic patients should be treated in interdisciplinary teams, optimally in neuropsychiatric units; additionally, specialists for endocrinology, diabetology and cardiology should be consulted for the frequently occuring somatic comorbidities. (3) Current diagnostic procedures and (4) therapies would have to be modified significantly. (5) There might be repercussions for the pharmaceutical industry as well: firstly, because old drugs with expired patent protection could partly replace expensive drugs and secondly because there would be a demand for the development of new anti-inflammatory drugs. (6) Legal evaluation of compulsory treatment orders might have to be reconsidered in light of causal therapies; leading to increased legal approval and reduced need for compulsory treatment orders due to better patient compliance. (7) The social inclusion of patients might improve, if treatment became more effective regarding cognitive and social functioning. (8) The stigmatization of patients and their relatives might decrease.